THE EFFECT OF ADDITION FISH FLOUR (Ilisha elongata) ON THE QUALITY OF BISCUIT - Usman Jujur Siregar; Sumarto Sumarto; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTBiang fish has the characteristic of having fine spines with a high amount of production (670,800 tons in 2019). The use of biang fish can be used as processed products as a food diversification effort, such as biscuit products. This study aimed to determine the best quality of biscuits added with biang fish flour using different concentrations of biang fish flour with organoleptic parameters. The study used an experimental method with the addition of a different source of fish meal, namely 0%, 2%, 4%, 6%, and 8%. The results showed that biscuits with the addition of 4% biang fish flour were the best treatment with a face value (8.83) with yellowish features, texture (8.60) with a mixture of brittle and dry, aroma (8.92) with a mixture of distinctive aromas biscuits and flavors, and taste (8.89) with delicious and savory characteristics.Keywords: biscuit, Ilisha elongata, fish folour..